"I Shut the Door": Interactions, tensions, and negotiations from a location-based social app. (July 2018) - Fitzpatrick, Colin; Birnholtz, Jeremy
Location-based social apps leverage mobile phones to provide face-to-face (FtF) social opportunities for physically proximate individuals, such as finding nearby people to socialize, date, or hook up. Prior work on dating and hookup apps has focused mostly on profiles and user goals, but this leaves open important questions of how, after constructing a profile, people use these apps to connect and realize their goals, and what these experiences are like. We report on 22 interviews with users of Grindr, a location-based social app for men who have sex with men. We examine interaction processes from viewing profiles to meeting up. Using the perspective of relational dialectics, we explore tensions around connecting with others, sharing information, and being predictable or novel. We find that profile presentations are flexible and subject to change, disinhibition challenges interaction and revealing goals, and social consequences increase through moving from profile browsing to meeting FtF.